Teachers’ formation for Higher Education and the diversity in the docence/teaching - Passos Alencastro Veiga, Ilma (Revista Diálogo Educacional, 2014)
The present article aims to analyze the formation of the teachers for the higher education and its relations with the diversity of teaching as a professional practice. The theme has been, slowly, questioned in the debate and ethics pedagogical and institutional practice. The teaching in the higher education is an undertaking that articulates different possibilities and demands pedagogical formation. I carry out a brief reading of the terms formation and teaching and presents an argument in favor of the nature and characteristics of the teaching, leaving show through an issue of diversity. To propose a start point for the formative process I chose six facets of the teaching that gave origin to this article, from the observations achieved in the lectures in the graduation courses, in the area of health. I conclude defending the temptation of the construction of some formative principles such as: the teaching represents an amalgam marked by public policies, considers the diversity, and is a social practice contextualized.